Moringa oleifera as a potential source of lecithin - Leong, Siew Yin (2012)
Lecithin in strict Scientific term refers to phosphatidyicholine. Lecithin which proves to provide sufficient amount of essential nutrients for the cells and biological functions of the body is also used in the food applications as food additives and stabilizers. The valuable properties of lecithin have created great demand and thus, attempt for new resources of lecithin from other plants has been done beside lecithin derived from soy beans. Moringa olefera have been known for its rich sources of nutrition values and uses in curing much kind of diseases are found grown in tropical and humid climates areas. Fixed oils from the M olefera seeds are extracted using Soxhlet extraction with hexane solvent. Results showed that the solvent-extracted mature M olefera seeds have highly of 30% oil, the immature M olefera seeds have 25.0% oil, and the soybean seeds have 19.5% of oil. Compare to the cold maceration extracted method, the mature M olefera seeds have 25.4% of oil, the immature M olefera seeds have 20.2% of oil, and the soybean seeds havel6.7% of oil. The percentage of total lecithin fraction (weight of pellet/weight of oil) showed that mature M olefera oil has 6.07%, immature M olefera has 4.96%, the soybean oil has 8.14% and the commercial soybean has 5.75% of phospholipids. The separation of individual phospholipid components of Moringa and soybean lecithin fraction were carried out using thin layer chromatography (TLC). The result showed Moringa lecithin contained 4-5 individual phospholipid and the presence of C=C group of fatty acid was found presence in Lane 1 and 2 of separated lecithin fraction of mature Moringa lecithin. Fatty acid compositions of Moringa seed oil, commercial soybean oil and Moringa lecithin (mature and immature) were determined using gas liquid chromatography (GLC). The result showed the relative percentage of fatty acid composition of Moringa oil (mature and immature) has higher stearic acid and oleic acid compare to the soybean oil as reported by a literature.